2015
DOI: 10.3329/fmcj.v9i1.23622
|View full text |Cite
|
Sign up to set email alerts
|

Role of CT scan in the evaluation of lung tumor with cytopathilogical correlation

Abstract: :Lung cancer is an important & widespread disease that contributes a major health problem worldwide. Lung cancer kills over 1 million people per year. Cigarette smoking is the major cause of lung cancer. CT scan is the principal radiological examination adjunct to X-Ray chest examination in diagnosis & management of lung cancer. The main Objective of the study was to assess the diagnostic usefulness of CT scan in evaluating & characterize the different types of lung tumors and to correlate CT findings of lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Both lungs were involved in four cases (4.4%). These findings are comparable to the study by Hoque et al, where maximum number of masses were detected in right upper zone (25.5%), followed by 19.6% in left upper zone [10]. In the study by Rawat et al both lungs were found to be involved in 2.96% of cases [9].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Both lungs were involved in four cases (4.4%). These findings are comparable to the study by Hoque et al, where maximum number of masses were detected in right upper zone (25.5%), followed by 19.6% in left upper zone [10]. In the study by Rawat et al both lungs were found to be involved in 2.96% of cases [9].…”
Section: Discussionsupporting
confidence: 86%
“…The youngest patients was 40 years old (2 cases) and the oldest was aged 100 years. The age of the cases with pulmonary mass lesions seen in various other studies ranged from 40 to above 80 years [8][9][10][11][12]. Smoking is found to be associated with 81.1% of patients with lung masses in this study.…”
Section: Discussionmentioning
confidence: 59%
“…Right lung predilection was reported in previous studies especially upper lobes. 2,3,15,17 The upper lobes susceptibility to lung cancer might be attributed to that the upper lobes are less vascular and more aerated than the lower ones, therefore it is more affected by smoking. 17 Lung masses was commonly detected in (50.0%, 46.2% and 40.6%) of our patients with SCLC, SCC and LCC respectively, while lung nodule was commonly detected in ADC (47.4 %) (p=0.06).…”
Section: Discussionmentioning
confidence: 99%
“…1 Cigarette smoking is the major cause of lung cancer; 95% of patients are smokers. 2 At presentation, 85% of the patients are symptomatic. 3 They may present with non-specific symptoms (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation